Self-perceived oral health among three subgroups of Asian-Americans in New York City: a preliminary study - Cruz GD, Galvis DL, Kim M, Le-Geros RZ, Barrow S-YL, Tavares M, Bachiman (2001)
The aim of this preliminary study was to compare the perception of oral health among subgroups of Asian-American residents of New York City, USA